2017
DOI: 10.5194/acp-17-11089-2017
|View full text |Cite
|
Sign up to set email alerts
|

Determination of enhancement ratios of HCOOH relative to CO in biomass burning plumes by the Infrared Atmospheric Sounding Interferometer (IASI)

Abstract: Abstract. Formic acid (HCOOH) concentrations are often underestimated by models, and its chemistry is highly uncertain. HCOOH is, however, among the most abundant atmospheric volatile organic compounds, and it is potentially responsible for rain acidity in remote areas. HCOOH data from the Infrared Atmospheric Sounding Interferometer (IASI) are analyzed from 2008 to 2014 to estimate enhancement ratios from biomass burning emissions over seven regions. Fire-affected HCOOH and CO total columns are defined by com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 81 publications
(127 reference statements)
0
13
0
Order By: Relevance
“…Over the biomass burning areas, the ratios are similarly close to 1, although higher fire emission factors for CH3COOH than for HCOOH are reported in the literature (Akagi et al, ; Andreae, ). While we cannot rule out potential retrieval biases, another explanation is a rapid secondary HCOOH formation, as suggested by space‐based pyrogenic HCOOH enhancement ratios that are significantly higher than expected (Chaliyakunnel et al, ; Pommier et al, ), and which would not be present to the same degree for CH3COOH.…”
Section: Resultsmentioning
confidence: 67%
“…Over the biomass burning areas, the ratios are similarly close to 1, although higher fire emission factors for CH3COOH than for HCOOH are reported in the literature (Akagi et al, ; Andreae, ). While we cannot rule out potential retrieval biases, another explanation is a rapid secondary HCOOH formation, as suggested by space‐based pyrogenic HCOOH enhancement ratios that are significantly higher than expected (Chaliyakunnel et al, ; Pommier et al, ), and which would not be present to the same degree for CH3COOH.…”
Section: Resultsmentioning
confidence: 67%
“…One main advantage of the ERs compared to the EFs is that ER calculation only requires simultaneous measurements of the studied (NH 3 ) and the reference species (CO), while EF calculation requires fuel information that is not always available or completely reliable (Andreae and Merlet, 2001). In fire plumes, ERs can be estimated following (Goode et al, 2000;R'Honi et al, 2013)…”
Section: Enhancement Ratiosmentioning
confidence: 99%
“…With a contribution estimated to be about 13 % (Galloway et al, 2004) of the total emissions, biomass burning is believed to be the second most important source of NH 3 after agriculture. From previous studies, it has been shown that biomass burning could significantly affect NH 3 concentrations in the atmosphere, especially in the tropics but also at higher latitudes (e.g., Bouwman et al, 1997;Coheur et al, 2009;Adon et al, 2010;Alvarado et al, 2011;Shephard et al, 2011;Adon et al, 2013;R'Honi et al, 2013;Whitburn et al, , 2016aBenedict et al, 2017;Warner et al, 2017). Excess NH 3 in the environment is of great concern since it is responsible for many environmental is-12240 S. Whitburn et al: ER NH 3 / CO in tropical biomass burning regions sues such as eutrophication of terrestrial and aquatic ecosystems, soil acidification, and loss of plant diversity (Aneja et al, 2001;Erisman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the focus is principally on CO, nitrogen dioxide (NO 2 ), and aerosols (e.g., Pechony et al, 2013;Castellanos et al, 2014;Ichoku and Ellison, 2014;Mebust and Cohen, 2014;Schreier et al, 2014a, b). A recent study was also dedicated to formic acid (HCOOH) (Pommier et al, 2017). Until now, less attention has been given to NH 3 Alvarado et al, 2011;R'Honi et al, 2013;Luo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%